Socio-demographic determinants and prevalence of Tuberculosis knowledge in three slum populations of Uganda - Obuku Ekwaro A; Meynell Clea; Kiboss-Kyeyune Jemimah; Blankley Simon; Atuhairwe Christine; Nabankema Evelyn; Lab Morris; Jeffrey Nikki; Ndungutse David (BMC, 2012)
Abstract Background Knowledge of tuberculosis has been shown to influence health seeking behaviour; and urban slum dwellers are at a higher risk of acquiring tuberculosis than the general population. The study aim was to assess knowledge of tuberculosis and identify the associated socio-demographic determinants, in order to inform tailored interventions for advocacy, communication and social mobilisation in three urban-slum communities of Uganda. Methods A cross-sectional survey of 1361 adults between April and October 2011. Data was analyzed by descriptive statistics. Adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) of potential determinants of tuberculosis (TB) knowledge were estimated by multivariable ordinal logistic regression using Stata 11.2 software. Results We found low knowledge of TB cause (26.7%); symptoms (46.8%), transmission (54.3%), prevention (34%) and free treatment (35%). Knowledge about TB treatment (69.4) and cure (85.1) was relatively high. Independent determinants of poor knowledge of TB in the multivariable analysis included (aOR, 95% CI) lack of formal education (0.56; 0.38 - 0.83, P = 0.004), unemployment (0.67; 0.49 - 0.90, P = 0.010) and never testing for HIV (0.69; 0.51 - 0.92, P < 0.012). Whilst, older age (1.73; 1.30 - 2.29, P < 0.001) and residing in Lira (2.02; 1.50 - 2.72, P < 0.001) were independent determinants of higher knowledge of TB. Conclusion This study revealed deficiencies in the public health knowledge about TB symptoms, diagnosis and treatment among urban-slum dwellers in Uganda. Tuberculosis control programmes in similar settings should consider innovative strategies for TB education, advocacy, communication and social mobilisation to reach the youth, unemployed and less-educated; as well as those who have never tested for HIV.